The best of I love toy trains. Parts 7-12 [videorecording (DVD)] - Coffey, James (TM Books & Video, Inc., 2013)
Visit the Grand Canyon Railroad, the Sugar Cane Train and the Aquarium in Maui, the Hesston Steam Museum in Indiana, and the Freedom Train traveling across America. See steamers puffing smoke, sleek diesels, funny toy train bloopers, and legendary toy trains like the Blue Cornet, Hiawatha, State Set, the fabulous Mayflower, and legendary art deco steamliners from the 30s.